Influence of Rotation on Heat Transfer from a Two-Pass Channel with Periodically Placed Turbulence and Secondary Flow Promoters - S. Dutta; J.-C. Han; Y.-M. Zhang (International Journal of Rotating Machinery)
In a stationary duct, ribs placed at an angle oblique to the main flow direction are more effective in heat transfer enhancement than the ribs placed perpendicular to the flow. Obliquely placed ribs, besides tripping the boundary layer, produce secondary flow patterns to increase heat transfer from the surfaces. Ducts rotating about an axis perpendicular to their own also develop secondary flows. These two secondary flows, produced by oblique ribs and rotation, interact with each other and develop a new heat transfer pattern that is different from those produced by oblique ribs or by rotation alone. This paper uses two types of rib configurations (60∘ parallel ribs and 60∘ staggered ribs) as turbulence and secondary flow promoters. The local and surface averaged Nusslt numbers are presented for both stationary and rotating conditions. This experimental study is conducted on a two-pass square channel with two opposite rib roughened surfaces (leading and trailing sides). All the walls are maintained at the same temperature. The heat transfer results in a rotating condition show that the 60∘ staggered ribs are more effective in the first pass but the 60∘ parallel ribs do better in the second pass.